Ultrasound Modulates the Splenic Neuroimmune Axis in Attenuating AKI - Gigliotti, Joseph C. (J Am Soc Nephrol, 2015)
We showed previously that prior exposure to a modified ultrasound regimen prevents kidney ischemia-reperfusion injury (IRI) likely via the splenic cholinergic anti-inflammatory pathway (CAP) and α7 nicotinic acetylcholine receptors (α7nAChR). However, it is unclear how ultrasound stimulates the splenic CAP. Further investigating the role of the spleen in ischemic injury, we found that prior splenectomy (–7d) or chemical sympathectomy of the spleen with 6-hydroxydopamine (6OHDA; –14d) exacerbated injury after subthreshold (24-minute ischemia) IRI. 6-OHDA–induced splenic denervation also prevented ultrasound-induced protection of kidneys from moderate (26-minute ischemia) IRI. Ultrasound-induced protection required hematopoietic but not parenchymal α7nAChRs, as shown by experiments in bone marrow chimeras generated with wild-type and α7nAChR(–/–) mice. Ultrasound protection was associated with reduced expression of circulating and kidney-derived cytokines. However, splenocytes isolated from mice 24 hours after ultrasound treatment released more IL-6 ex vivo in response to LPS than splenocytes from sham mice. Adoptive transfer of splenocytes from ultrasound-treated (but not sham) mice to naïve mice was sufficient to protect kidneys of recipient mice from IRI. Ultrasound treatment 24 hours before cecal ligation puncture–induced sepsis was effective in reducing plasma creatinine in this model of AKI. Thus, splenocytes of ultrasound-treated mice are capable of modulating IRI in vivo, supporting our ongoing hypothesis that a modified ultrasound regimen has therapeutic potential for AKI and other inflammatory conditions.